Contemporary Management of Complex Ventricular Arrhythmias - Benedict M Wiles; Anthony C Li; Michael C Waight; Magdi M Saba (Arrhythmia & Electrophysiology Review)
Percutaneous catheter ablation is an effective and safe therapy that can eliminate ventricular tachycardia, reducing the risks of both recurrent arrhythmia and shock therapies from a defibrillator. Successful ablation requires accurate identification of arrhythmic substrate and the effective delivery of energy to the targeted tissue. A thorough pre-procedural assessment is needed before considered 3D electroanatomical mapping can be performed. In contemporary practice, this must combine traditional electrophysiological techniques, such as activation and entrainment mapping, with more novel physiological mapping techniques for which there is an ever-increasing evidence base. Novel techniques to maximise energy delivery to the tissue must also be considered and balanced against their associated risks of complication. This review provides a comprehensive appraisal of contemporary practice and the evidence base that supports recent developments in mapping and ablation, while also considering potential future developments in the field.